Rancangan Game RPG ”Legenda Putri Petung” Menggunakan RPG Maker MV - Arham, Muhammad Agus Faadhilah; Fajri, Ahmad; Wahyuni, Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Games have become a popular entertainment alternative for various groups, with very rapid development. This research focuses on the creation of a Role-Playing Game (RPG), which is known for its complex story elements and strong role immersion. The purpose of this research is to develop an RPG based on the East Kalimantan folktale